Insights into ABA-mediated regulation of guard cell primary metabolism revealed by systems biology approaches. (September 2019) - Yoshida, Takuya; Anjos, Letícia dos; Medeiros, David B.; Araújo, Wagner L.; Fernie, Alisdair R.; Daloso, Danilo M.
Abstract: Despite the fact that guard cell abscisic acid (ABA) signalling pathway is well documented, our understanding concerning how and to which extent ABA regulates guard cell metabolism remains fragmentary. Here we have adopted different systems approaches to investigate how ABA modulates guard cell central metabolism by providing genes that are possibly ABA-regulated. By using previous published Arabidopsis guard cell transcript profiling data, we carried out an extensive co-expression network analysis using ABA-related genes and those related to the metabolism and transport of sugars, starch and organic acids. Next, we investigated the presence of ABA responsive elements (ABRE) in the promoter of genes that are highly expressed in guard cells, responsive to ABA and co-expressed with ABA-related genes. Together, these analyses indicated that 44 genes are likely regulated by ABA and 8 of them are highly expressed in guard cells in both the presence and absence of ABA, including genes of the tricarboxylic acid cycle and those related to sucrose and hexose transport and metabolism. It seems likely that ABA may modulate both sucrose transport through guard cell plasma membrane and sucrose metabolism within guard cells. In this context, genes associated with sucrose synthase, sucrose phosphate synthase, trehalose-6-phosphate, invertase, UDP-glucose epimerase/pyrophosphorylase and different sugar transporters contain ABRE in their promoter and are thus possibly ABA regulated. Although validation experiments are required, our study highlights the importance of systems biology approaches to drive new hypothesis and to unravel genes and pathways that are regulated by ABA in guard cells.